The effect of balanced electrolyte solution versus normal saline in the prevention of hyperchloremic metabolic acidosis in diabetic ketoacidosis patients: a randomized controlled trial (Medical Journal of Indonesia, 2017)
Background: In resuscitation, normal saline could cause hyperchloremic metabolic acidosis, while balanced electrolyte solution is a crystalloid fluid resembling blood plasma with lower chloride content. This study compared the effect of normal saline and balanced electrolyte solution Ringerfundin (BES) as the resuscitation fluid in diabetic ketoacidosis (DKA) patients. Parameters applied in this study were standard base excess (SBE) as resuscitationâs result indicator and strong ion difference (SID) to measure chlorideâs influence in developing hyperchloremic acidosis.Methods: A prospective, randomized, single blind controlled trial was conducted at the Emergency Department of Cipto Mangunkusumo Hospital. Thirty subjects with blood sugar >250 mg/dl, arterial pH <7.35 mg/dl, and positive blood ketone were randomly allocated to receive either normal saline (NS) or RingerfundinÃ (BES) as the standardized resuscitation protocol. Data analysis was performed using the unpaired T-test and the Mann Whitney test to compare the SBE and the SID means between both groups. Additional parameters were the level of consciousness, blood sugar level, vital signs, blood gas analysis, lactate, electrolyte, and blood ketone.Results: The mean SID in the BES group was significantly greater than the NS group of all measurements (p<0.05). The BES group had significantly higher mean SBE compared to the NS group at 18 hours (-4.88Â±5.69 vs -9.68Â±5.64; p=0.009), 24 hours (-3.99Â±4.27 vs -8.7Â±5.35; p=0.023), and 48 hours (-4.06Â±4.11 vs -7.01Â±5.46; p=0.009). BES resulted in non-significant higher delta SBE and SID than NS. Additional parameters were not different between both groups.Conclusion: This study showed that fluid resuscitation of DKA patients with BES resulted in slightly but not significantly higher mean actual SBE and SID than NS. suggesting that BES as an alternative fluid resuscitation to prevent hyperchloremic acidosis in diabetic ketoacidosis patients was not superior to NS.